Adenylyl cyclase-mediated effects contribute to increased Isoprenaline-induced cardiac contractility in TRPM4-deficient mice - Uhl, Sebastian; Mathar, Ilka; Vennekens, Rudi; Freichel, Marc (Journal of molecular and cellular cardiology, 2014)
TRPM4 and TRPM5 proteins belong to the Transient Receptor Potential (TRP) ion channel family and form Ca2+-activated nonselective cation channels. Recently we showed a significant increase of Isoprenaline-induced inotropy in TRPM4-deficient (Trpm4−/−) mice. This is caused by increased Ca2+ entry via L-type calcium channels due to faster action potential repolarization in Trpm4−/− ventricular myocytes [Mathar et al., 2013]. Here, we investigated the contribution of various steps of the β-adrenergic signalling cascade to the augmented positive inotropic response in the absence of TRPM4, and whether the closely related TRPM5 additively contributes to this process using TRPM4/TRPM5-double deficient (Trpm4/Trpm5(−/−)2) mice. We performed contractility measurements on isolated papillary muscles from wild type, Trpm4−/− and Trpm4/Trpm5(−/−)2 mice. As shown in Trpm4−/− mice, Isoprenaline-induced inotropy in Trpm4/Trpm5(−/−)2 papillary muscles was significantly increased compared to wild type, whereas basal, frequency- and Ca2+-dependent contractility was unaltered. Equivalent to Isoprenaline, activation of adenylyl cyclase using Forskolin led to a significantly increased twitch force in Trpm4−/− heart preparations whereas the Isoprenaline-mediated increase in cAMP level was comparable to wild type mice. Notably, the positive inotropic response evoked by phosphodiesterase inhibition with 3-isobutyl-1-methylxanthine (IBMX) was unchanged between both genotypes. Furthermore, experiments performed with increasing concentrations of IBMX after prestimulation with Forskolin and vice versa did not provide evidence that the increased β-adrenergic positive inotropic response in TRPM4-deficient papillary muscles is due to differences in accumulation of cAMP. Compared to inhibition of phosphodiesterase, the rise of intracellular cAMP by activating adenylyl cyclase is accompanied by ATP breakdown. To test the relevance of TRPM4 during forced ATP consumption we measured contractility under ischemic conditions. Here, Trpm4−/− papillary muscles showed improved contractile function in comparison to wild type. Our results are consistent with the hypothesis that TRPM4 has a limiting effect on cardiac contractility specifically in ATP depleting conditions. The increased positive inotropic response in Trpm4−/− papillary muscles evoked by stimulation of adenylyl cyclase activity is not observed without active enhancement of ATP hydrolysis. Furthermore, the contractility of Trpm4−/− papillary muscles was also increased during ischemic simulation. These data underscore the potential of TRPM4 inactivation as an approach to increase inotropy in specific conditions associated with increased catecholamine levels, such as heart failure and ischemia.